2006
DOI: 10.1016/j.ijgo.2006.04.035
|View full text |Cite
|
Sign up to set email alerts
|

Active management of labor in a low‐resource setting and its impact on cesarean section rates

Abstract: Labor and delivery-related complications being the largest contributors to India's high maternal mortality rate, optimizing labor and delivery are of utmost importance. This study analyses the safety and efficacy of active management of labor at a secondary hospital using the protocol proposed by Daftary [1].Women in labor with a term pregnancy who consented to the protocol formed the study group. The control group was managed expectantly. The 2 groups of 700 participants each were similar regarding parity, ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 1 publication
0
7
0
Order By: Relevance
“…Here it is given along with an analgesic agent like tramadol, as the combined drug effect is considered to provide good analgesia, in addition to improving the cervical dilatation. 11,12 Camylofin injection can be used for augmentation of labor in both primigravida and multigravida women. Camylofin shortens the duration of labor in primigravidas by almost 40% and multigravidas by almost 24%.…”
Section: Indications and Clinical Usementioning
confidence: 99%
See 3 more Smart Citations
“…Here it is given along with an analgesic agent like tramadol, as the combined drug effect is considered to provide good analgesia, in addition to improving the cervical dilatation. 11,12 Camylofin injection can be used for augmentation of labor in both primigravida and multigravida women. Camylofin shortens the duration of labor in primigravidas by almost 40% and multigravidas by almost 24%.…”
Section: Indications and Clinical Usementioning
confidence: 99%
“…Driscoll et al reported on the advantages of active management of labor resulting in shorter labor, improved obstetric outcome and lowered cesarean section rates. 11,12,20…”
Section: Active Management Of Labormentioning
confidence: 99%
See 2 more Smart Citations
“…3 In obstetric practice it not only hastens cervical dilatation for augmentation of labor, but also provides enhanced analgesia when given along drugs like tramadol. 4,5,6 Camylofin has been available in India since 1958. 7 Ever since, the drug has traversed almost six decades of clinical use and continues to be a preferred antispasmodic for a variety of spasmodic pains of abdominal origin.…”
mentioning
confidence: 99%